Generation of Energy-Modulated Electron Beam from the Photocathode RF Gun and its Application for Free Electron Lasers - FURUKAWA, Hiroyuki; IMASAKI, Kazuo; CHEN, Jizhong; YAMANAKA, Chiyoe; FUJITA, Masayuki; OHKUBO, Koichi; NAKAI, Sadao (Rēzā kenkyū, 1998)
By modulating the laser beam profile in space and time, the photocathode RF gun enables us to control the electron beam in space, time and also energy. We have numerically investigated the generation and acceleration of the energy-modulated electron bunch in the RF linac system. Adjusting the input laser beam profile and the acceleration phase, possibility of producing the 9 MeV electron bunch with energy modulation was demonstrated by the simulation code LUNA. The energy-modulated electron beam can be used to enhance the efficiency of the free electron lasers (FELs) with the optical klystron. Especially, the single-pass FELs in VUV region, which rely on the scheme of the self-amplified spontaneous emission, have benefit in shortening the wiggler length.